Design Simulation of Upper Arm on Welding Table - Arifin, Fatahul; Azharuddin; Arnoldi, Dwi; Effendi, Sairul; Herlambang, Yusuf Dewantoro; Yahya; Muhammad Arif Fadilah; Radjiq, Akhmad (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2023)
Welding process is the joining of two metals by heating. There are two types of welding that are often applied in the field, namely gas welding (OAW) and electric welding (SMAW). Both of them have their advantages as metal connectors. This research originated from a problem that occurred in the upper arm on the welding table which experienced bending as a result of carrying the load when holding the welding disc. Therefore, CAD/CAE design is carried out. In this case, the strength and tension that occur in the upper arm are analyzed. This research aims to reveal the value of the stress that occurs in the upper arm and the safety value. Where in the design the planned force capacity is 300 newtons using the finite element method or also known as Finite Element Analysis (FEA). And the material used is ASTM A36. The results of the simulation and also the analysis that has been carried out show that the upper arm frame structure on the welding table has a stress, deformation, and safety factor of 311.987 MPa, 2.28286 mm, and 0.663488 ul.